Periodontitis Risk Variants at SIGLEC5 Impair ERG and MAFB Binding. (May 2022) - Mueller, R.; Chopra, A.; Dommisch, H.; Schaefer, A.S.
Periodontitis is a common complex inflammatory disease of the oral cavity. It is characterized by inflammation of gingival tissues and alveolar bone loss. Recently, a genome-wide association study and 2 genome-wide association study meta-analyses found 2 associated regions (haplotype blocks) at the inhibitory immune receptor gene SIGLEC5 to increase the risk for periodontitis. The aims of the current study were the identification of the putative causal variants underlying these associations, characterization of their molecular biological effects, and validation of SIGLEC5 as the target gene. We mapped the associated single-nucleotide polymorphisms to DNA elements with predictive features of regulatory functions and screened the associated alleles for transcription factor (TF) binding sites. Antibody electrophoretic mobility shift assays (EMSAs) with allele-specific probes were used to identify TF binding and to quantify allele-specific effects on binding affinities. Luciferase reporter assays were used to quantify the effect directions and allele-specific strength of the associated regulatory elements. We used CRISPR-dCas9 gene activation to validate SIGLEC5 as a target of the association. EMSA in peripheral blood mononuclear cells showed that E-26 transformation–specific TF-related gene (ERG) binds at rs11084095, with almost complete loss of binding at the minor A-allele. Allele-specific reporter genes showed enhancer function of the DNA sequence at rs11084095, which was abrogated in the background of the A-allele. EMSA in B lymphocytes showed that TF MAF bZIP (MAFB) binds at the common G-allele of rs4284742, whereas the minor A-allele reduced TF binding by 69%, corresponding to 9-fold reduction of luciferase reporter gene activity by the A-allele. Using CRISPR-dCas9, we showed that the enhancer at rs4284742 strongly activated SIGLEC5 expression, validating this gene as the target gene of the association. We conclude that rs11084095 and rs4284742 are putatively causal for the genome-wide significant associations with periodontitis at SIGLEC5 that impair ERG and MAFB binding, respectively.